2011
DOI: 10.1158/1541-7786.mcr-10-0512
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic Screen Identifies Potential Therapeutic Targets in Melanoma

Abstract: Therapies directed against receptor tyrosine kinases are effective in many cancer subtypes, including lung and breast cancer. We used a phospho-proteomic platform to identify active receptor tyrosine kinases that might represent therapeutic targets in a panel of twenty-five melanoma cell strains. We detected activated receptors including TYRO3, AXL, MERTK, EPHB2, MET, IGF1R, EGFR, KIT, HER3, and HER4. Statistical analysis of receptor tyrosine kinase activation as well as ligand and receptor expression indicate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 41 publications
5
82
0
Order By: Relevance
“…In agreement with a previous report demonstrating phosphorylation of TAM family receptors in several melanoma cell lines (16), the data presented here confirm that MERTK can be phosphorylated in melanoma cells and further show that MERTK is functionally important for several oncogenic signaling pathways and phenotypes. Specifically, we report here on MERTK-mediated signaling through the MAPK/ERK, PI3K/ AKT, and JAK/STAT signaling pathways.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with a previous report demonstrating phosphorylation of TAM family receptors in several melanoma cell lines (16), the data presented here confirm that MERTK can be phosphorylated in melanoma cells and further show that MERTK is functionally important for several oncogenic signaling pathways and phenotypes. Specifically, we report here on MERTK-mediated signaling through the MAPK/ERK, PI3K/ AKT, and JAK/STAT signaling pathways.…”
Section: Discussionsupporting
confidence: 93%
“…Although MERTK expression has been previously demonstrated in several melanoma cell lines (16), its expression in melanoma tissues has not been previously reported. To investigate the pattern and expression levels of MERTK during nevusto-melanoma progression, 2 independent tissue microarrays…”
Section: Mertk Expression Increases With Melanoma Progression From Nementioning
confidence: 89%
See 1 more Smart Citation
“…9,10 AXL is frequently overexpressed in human cancers including lymphocytic leukemia, breast, colon, skin, thyroid and prostate cancer. [11][12][13][14][15][16][17] Down-regulation of AXL by siRNA attenuates the migration and invasion of breast, 18 ovarian, 19 hepatocellular carcinoma, 20 mesothelioma, 21 prostate 22 and pancreatic cancer. 23 Furthermore it has been shown that the inhibition of AXL results in the reduction of cancer progression and metastatic potential and induces apoptosis in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…At least one study has shown that TAM and other tyrosine kinase receptors are activated in melanoma, 6 and two more have linked TYRO3, AXL and the TAM receptor ligand, growth arrest-specific 6 (GAS6), to melanoma tumorigenesis and invasiveness. 7,8 Collectively, these findings prompted Douglas Graham and colleagues to hypothesize that MERTK might also be a therapeutic target in melanoma.…”
mentioning
confidence: 99%